2022
DOI: 10.1021/acsinfecdis.2c00052
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of the Antifungal Activity of Chitinase by Palmitoylation and the Synergy of Palmitoylated Chitinase with Amphotericin B

Abstract: Combinations of antifungal drugs can have synergistic antifungal activity, achieving high therapeutic efficacy while minimizing the side effects. Amphotericin B (AMB) has been used as a standard antifungal drug for fungal infections; however, because of its high toxicity, new strategies to minimize the required dose are desirable. Chitinases have recently received attention as alternative safe antifungal agents. Herein, we report the combination of palmitoylated chitinase domains with AMB to enhance the antifu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 42 publications
3
11
0
Order By: Relevance
“…The cytotoxicity against mammalian cells did not change by anchoring LysM-Pal on AmBisome, suggesting that the state of AmB in AmBisome was not significantly altered by anchoring LysM-Pal. In our previous report, we confirmed that 1 μM LysM-Pal with 5 μM Fungizone, micellar formulation of amphotericin B solubilized with sodium deoxycholate and is more cytotoxic than AmBisome, did not show cytotoxicity against mammalian cells . Moreover, we have evaluated the cytotoxicity of various lipidated EGFP against SNU-6 cells at a concentration of 1 μM and all lipids including C16 showed no cytotoxicity .…”
Section: Resultssupporting
confidence: 67%
See 3 more Smart Citations
“…The cytotoxicity against mammalian cells did not change by anchoring LysM-Pal on AmBisome, suggesting that the state of AmB in AmBisome was not significantly altered by anchoring LysM-Pal. In our previous report, we confirmed that 1 μM LysM-Pal with 5 μM Fungizone, micellar formulation of amphotericin B solubilized with sodium deoxycholate and is more cytotoxic than AmBisome, did not show cytotoxicity against mammalian cells . Moreover, we have evaluated the cytotoxicity of various lipidated EGFP against SNU-6 cells at a concentration of 1 μM and all lipids including C16 showed no cytotoxicity .…”
Section: Resultssupporting
confidence: 67%
“…In our previous report, we confirmed that 1 μM LysM-Pal with 5 μM Fungizone, micellar formulation of amphotericin B solubilized with sodium deoxycholate and is more cytotoxic than AmBisome, did not show cytotoxicity against mammalian cells. 28 Moreover, we have evaluated the cytotoxicity of various lipidated EGFP against SNU-6 cells at a concentration of 1 μM and all lipids including C16 showed no cytotoxicity. 27 These results indicate that LysM-AmBisome may not show adverse effects on mammalian cells and can be used in the same way as AmBisome.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These results suggest that dipicolinic acid can be a suitable complement to reduce the concentration and use of carbendazim. These results can be explained considering that dipicolinic acid is capable of damaging F. sulawense cell wall, which may facilitate the entry of carbendazim inside the pathogen cells [ 67 ]. As far as we know, this is the first study regarding the combination of carbendazim and dipicolinic acid for the control of fungal diseases.…”
Section: Discussionmentioning
confidence: 99%